FRI0227 Characteristics, treatment and outcome of GI involvement in behcet syndrome: Experience in a dedicated center. (23rd January 2014) - Hatemi, I.; Hatemi, G.; Erzin, Y.; Ferhat Celik, A.; Yazici, H.
Abstract : Background: Gastrointestinal involvement can be a severe complication of Behcet's syndrome (BS) resulting in perforation and massive bleeding. Controlled data regarding treatment is lacking and long term prognosis is not well known. Objectives: To report the demographic and disease characteristics, type of involvement, treatment modalities and outcome of BS patients with gastrointestinal involvement (GIBS). Methods: We retrospectively reviewed the charts of all BS patients evaluated by gastroenterologists in our multidisciplinary BS clinic with a suspicion of gastrointestinal involvement, and surveyed those with a diagnosis of GIBS. Patients were evalauted either in the outpatient clinic or if not possible by phone calls to assess their outcome. Results: There are more than 8000 recorded BS patients in our multidisciplinary outpatient clinic. 69 of them had symptoms suggesting gastrointestinal involvement and lesions on endoscopy. Among these 18 patients had other reasons for their gastrointestinal symptomes and endoscopic lesions like non-steroidal anti-inflammatory drug use, gastrointestinal tuberculosis and antibiotic associated hemorhagic colitis. The remaining 51 patients had GIBS (Table ). The presenting symptoms were acute abdomen caused by perforations in 4/51 patients, massive bleeding in 8/51 patients and abdominal pain and/or diarrhea in 39/51 patients. Surgery had to be performed in 20/51 patients. The most commonly used drugs for initial management were azathioprine 2-2.5 mg/kg/day (n=33) and 5 ASA compounds 3-4 g/day (n=13). Remission was observed and there were no relapses during a mean follow-up of 44.3±46.9 months in 22/33 (67%) patients who had initially been prescribed azathioprine (2.5 mg/kg) and during 45.0±50.1 months in 9/13 (68%) patients who had been prescribed 5 ASA compounds. Other than the 33 patients who used azathioprine as their initial treatment, remission was also obtained with azathioprine in 3/4 patients who were resistant to 5 ASA compounds. Among the 10 patients who had relatively severe symptoms and persistent large ulcers despite at least 6 months of azathioprine treatment, endoscopic and symptomatic remission could be obtained with thalidomide in 4 patients, infliximab in 4 patients and adalimumab in 2 patients. After a mean follow-up of 7.1±4.8 years (range 0.25–17 years), 42 (84%) patients were in remission and 14 (28%) of these were off treatment. Four (8%) patients were still active, 3 (6%) patients had died due to non-GI releated reasons and 2 (4%) were lost to follow-up. Conclusions: 84% of patients with GIBS were in remission after a mean of 7 years of follow-up. Surgery was required in 40% of patients with GIBS. 5 ASA compounds or azathioprine provided remission and prevented relapses in two thirds of the patients. The latter was also beneficial in some patients resistant to 5 ASA compounds. Resistant and relapsing cases could be managed with thalidomide or TNF-alpha antagonists. Disclosure of Interest: None Declared